Assessment of the control measures for category A diseases of Animal Health Law: Lumpy Skin Disease. (24th January 2022) - ,; Nielsen, Søren Saxmose; Alvarez, Julio; Bicout, Dominique Joseph; Calistri, Paolo; Canali, Elisabetta; Drewe, Julian Ashley; Garin‐Bastuji, Bruno; Gonzales Rojas, José Luis; Gortázar Schmidt, Christian; Herskin, Mette; Michel, Virginie; et al.
Abstract: EFSA received a mandate from the EC to assess the effectiveness of some of the control measures against diseases included in the Category A list according to Regulation (EU) 2016/429 on transmissible animal diseases ('Animal Health Law'). This opinion belongs to a series of opinions where these control measures are assessed, with this opinion covering the assessment of control measures for Lumpy Skin Disease (LSD). In this opinion, EFSA and the AHAW Panel of experts review the effectiveness of: i) clinical and laboratory sampling procedures, ii) monitoring period and iii) the minimum radius of the protection and surveillance zones, and the minimum length of time that measures should be applied in these zones. The general methodology used for this series of opinions has been published elsewhere; nonetheless, the transmission kernels used for the assessment of the minimum radius of the protection and surveillance zones are shown. Several scenarios for which these control measures had to be assessed were designed and agreed prior to the start of the assessment. The monitoring period was assessed as effective, and based on the transmission kernels available, it was concluded that the protection zone of 20 km radius and the surveillance zone of 50 km radius would comprise > 99% of the transmission from an affected establishment if transmission occurred. Recommendations provided for each of the assessed scenarios aim to support the European Commission in the drafting of further pieces of legislation, as well as for plausible ad hoc requests in relation to LSD.